Innovation And Development Of Video Learning Media In Islamic Education: Potential And Practice - Yusawinur Barella; Muh. Khalifah Mustami; M.Yusuf T (Sean Institute, 2024)
Islamic education often requires a contextual approach that is relevant to the developments of the times to enhance the effectiveness of teaching and learning. This article examines the potential and practice of developing video learning media in the context of Islamic education. The study aims to understand how the integration of video as a learning medium can enrich the Islamic educational process and make it more interactive and appealing. The method used is the analysis of relevant literature. The research results show that the use of video not only supports better visibility of the teaching material but also enhances the understanding and retention of student knowledge. Additionally, the development of creative video content that aligns with Islamic values has proven significant in improving student motivation and engagement. This article suggests that the integration of video learning media in Islamic education should be carried out with careful consideration of content, cultural context, and Islamic values.